Comparative analysis of nutritional content in common chocolate brands in India - Rahul Hegde; Karibasappa GN; Pritesh Gawali; Riya Ramgade; Neha Pitale (Contemporary Pediatric Dentistry, 2025)
Aim: Chocolate is widely consumed, especially by children. While moderate intake may have benefits, excessive consumption is linked to dental caries. This study aimed to assess and compare total sugar, fat, and energy content in various chocolate confectioneries, evaluate correlations among these components, and examine consistency between product packaging and manufacturer-reported values. Methods: A cross-sectional analysis was conducted on a randomized sample of five chocolate types: dark, white, milk chocolate, toffees, and coated wafers. Products were selected from major retailers based on inclusion criteria requiring clear nutritional labeling and brand familiarity. In total, 56 products were analyzed. Nutritional values (per 100 g) for sugar, fat, and energy were collected from packaging and verified with data from official manufacturer websites. Descriptive statistics summarized nutrient content by category. Chisquare tests evaluated differences among chocolate types. Pearson correlation assessed relationships between sugar, fat, and energy content. Statistical analysis was performed using SPSS (version X), with significance set at p < 0.05. Results: Mean sugar content was 47.94 ± 9.68 g, highest in toffees (58.98 g), lowest in coated wafers (37.10 g). Mean fat was 29.06 ± 8.39 g, highest in milk chocolate (31.24 g), lowest in toffees (18.60 g). Energy content was highest in milk chocolate (530.33 Kcal) and lowest in coated wafers (453.00 Kcal). Significant differences were found in sugar (p < 0.001), fat, and energy content (p = 0.027). Sugar was negatively correlated with fat (-0.603) and energy (-0.259), while fat and energy were positively correlated (0.865). Conclusions: Parents and children should be informed about the nutritional content of chocolates. Excessive intake may contribute to caries and systemic health issues. Reading labels and making informed choices is essential for healthier consumption.